HUBUNGAN PEMBERIAN MPASI HOMEMADE DAN MPASI PABRIK DENGAN KENAIKAN BERAT BADAN BAYI USIA 6-12 BULAN DI PUSKESMAS BOJONG KABUPATEN BOGOR - Rizki Putri Rahmadhanti (2024)
Nutritional status is a sign of successful health development in the world, the source of nutrition in children aged 0-24 months can be obtained through breast milk and complementary foods given to children. Weight gain can be used to determine the category of children aged 0-24 months who are at risk of growth failure and the risk of stunted. The purpose of this study was to determine the relationship between the provision of homemade and factory complementary food with weight gain in infants aged 6-12 months at Bojong Health Center. This study used a cross-sectional approach with a consecutive sampling technique with a sample size of 30 respondents. Consumption of homemade complementary food and factory complementary food were 50% each. The nutritional values of energy, protein, and vitamins from both types of complementary food met the RDA for infant days. Fisher's exact test results showed no significant relationship between the provision of both types of complementary food and infant weight gain (ρ = 0.651 > 0.05). Thus, it can be concluded that the nutritional content of both types of complementary food is in accordance with the RDA values, except for the nutrients vitamin B6, calcium, iron, and zinc which have lower values in factory complementary foods. Also, there was no significant relationship between homemade and factory complementary food feeding on infant weight gain.